Emotion dysregulation, impulsivity and personality disorder traits: A community sample study. (August 2018) - Garofalo, Carlo; Velotti, Patrizia; Callea, Antonino; Popolo, Raffaele; Salvatore, Giampaolo; Cavallo, Francesca; Dimaggio, Giancarlo
Highlights: We examined the independent contribution of emotion dysregulation (ED) dimensions on PD traits. Emotional nonacceptance was transversally related to various PD traits. Unique profiles of ED differentiated cluster A, B, and C PD traits. Impulsivity explained incremental variance in schizotypal, borderline, and antisocial PD traits. Histrionic, narcissistic, and obsessive-compulsive PD traits were related to lower ED and impulsivity. Abstract: The present study was designed to test an emotion regulation framework to understand individual differences in personality disorder (PD) traits in a non-clinical sample. Specifically, we tested whether: selected dimensions of emotion dysregulation were differentially related to PD traits; and whether emotion dysregulation and impulsivity had independent associations with PD traits. A community sample of 399 individuals (mean age = 37.91; 56.6% males) completed self-report measures of PDs, emotion dysregulation and impulsivity. Emotion dysregulation facets and impulsivity had uniform bivariate associations with PD traits, but also evidenced unique associations in multiple regression analyses. Nonacceptance of emotional responses was the emotion dysregulation dimension underlying a wide array of PD. A limited repertoire of effective emotion regulation strategies was characteristic of cluster C PD, whereas emotional unawareness distinctly predicted schizoid PD. Antisocial PD traits were uniquely related to difficulties controlling impulsive behavior when upset. Finally, histrionic, narcissistic, and obsessive-compulsive PD were related to better self-reported emotion regulation. Impulsivity further explained a significant amount of variance in schizotypal, antisocial, borderline (positively), and obsessive-compulsive PD traits (negatively). If replicated in clinical samples, our findings will support the usefulness of targeting both emotional dysregulation and impulsivity in PDs psychotherapy.